1999
DOI: 10.1007/s001250051280
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C effects on nerve function, perfusion, Na + ,K + -ATPase activity and glutathione content in diabetic rats

Abstract: Changes in protein kinase (PK) C activity have been implicated in the complications of diabetes mellitus.In retina, blood vessels, kidney and heart, PKC activity is increased [1], perhaps due to raised de novo synthesis of diacylglycerol (DAG). A recent study has shown that PKC inhibitor treatment prevented the development of impaired retinal blood flow, renal glomerular hyperfiltration and microalbuminuria in diabetic rats [2] and this is compatible with the notion that PKC activation contributes to the aetio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
89
2
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 54 publications
7
89
2
1
Order By: Relevance
“…All three mechanisms contribute to enhanced oxidative and nitrosative stress (4,5,7,9 -11) resulting from imbalance between production and neutralization of reactive oxygen species. Enhanced oxidative stress has been documented in peripheral nerve (4,5,8,(12)(13)(14), dorsal root and sympathetic ganglia (15), and vasculature (16,17) of the peripheral nervous system and has been implicated in neurovascular dysfunction and motor and sensory nerve conduction velocity (MNCV and SNCV) deficits, impaired neurotrophic support, nerve metabolic and signal transduction changes, and morphologic abnormalities characteristic for diabetes (4,5,12,14,16 -20). Evidence for the pathophysiologic role of reactive nitrogen species in PDN is also emerging (16,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All three mechanisms contribute to enhanced oxidative and nitrosative stress (4,5,7,9 -11) resulting from imbalance between production and neutralization of reactive oxygen species. Enhanced oxidative stress has been documented in peripheral nerve (4,5,8,(12)(13)(14), dorsal root and sympathetic ganglia (15), and vasculature (16,17) of the peripheral nervous system and has been implicated in neurovascular dysfunction and motor and sensory nerve conduction velocity (MNCV and SNCV) deficits, impaired neurotrophic support, nerve metabolic and signal transduction changes, and morphologic abnormalities characteristic for diabetes (4,5,12,14,16 -20). Evidence for the pathophysiologic role of reactive nitrogen species in PDN is also emerging (16,21).…”
mentioning
confidence: 99%
“…Improved blood glucose control reduces the risk of peripheral diabetic neuropathy (PDN), thereby implicating hyperglycemia as a leading causative factor. Diabetic hyperglycemia causes PDN via several mechanisms, among which increased aldose reductase (AR) activity (2)(3)(4)(5), nonenzymatic glycation/glycoxidation (6,7), and activation of protein kinase C (2,8) are the best studied. All three mechanisms contribute to enhanced oxidative and nitrosative stress (4,5,7,9 -11) resulting from imbalance between production and neutralization of reactive oxygen species.…”
mentioning
confidence: 99%
“…These concentrations were not affected by PJ34 treatment in control or diabetic rats. [17] and PKC [22], with antioxidants [23] and with other agents, all indicating that consequences of diabetic hyperglycaemia such as increased sorbitol pathway activity, oxidative stress and PKC activation do not cause irreversible changes in the peripheral nervous system, at least in the early stage of PDN. More recently, it has been shown that intervention even further downstream than hyperglycaemia, at the level of oxidative-stress-initiated, mitogen-activated protein kinase signalling cascade, successfully restores normal nerve function [24].…”
Section: Resultsmentioning
confidence: 94%
“…In contrast, the effect of PARP inhibitor on nerve perfusion, manifested by a 17% increase in NBF and the absence of a significant increase in vascular conductance, was modest. While studies from several groups [17,22,23,27,28,36], including one from our laboratory [17], suggest that vascular factor plays an important role in MNCV and SNCV deficits in PDN, growing evidence indicates that the aetiology of diabetes-induced nerve dysfunction is far more complex, and involves both vascular and non-vascular mechanisms. In particular, in diabetic and galactosaemic transgenic mice overexpressing aldose reductase (AR) specifically in the Schwann cells of the peripheral nerve under the control of the rat myelin protein zero promoter, there was a significantly greater reduction in MNCV than in the corresponding groups of non-transgenic mice with normal AR content [37].…”
Section: Resultsmentioning
confidence: 94%
“…Como o aumento da atividade da PKC nos vasa nervorum leva à maior resposta contrátil e redução da vasodilatação, foram realizados estudos utilizando inibidores da PKC, os quais demonstraram efeito positivo sobre a condução nervosa, o que se atribuiu à melhora do fluxo sangüíneo aos nervos (42,43).…”
Section: Fluxo Sangüíneo Vascularunclassified